Islamic Legal Philosophy as a Framework for Legal Reform in Multicultural Societies - Yusuf, Nasruddin (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
Studies on the philosophy of Islamic law often remain descriptive-normative and repetitive, offering limited guidance for reform in lived legal settings. In Indonesia's multicultural and legally plural society - where state law, Islamic norms, and local adat interact - this gap becomes more consequential, because reform must sustain religious legitimacy while remaining socially workable across diverse communities. This article argues that Islamic legal philosophy can function as a systematic paradigm for Islamic legal reform when articulated through three dimensions: first, an ontological dimension that frames Islamic law as rooted in revelation and enlivened by reason; second, an epistemological dimension that explains lawful discovery through istinbat and istitdal, including the use of maqasid al-shariah and maslahah to engage new issues; and third, an axiological dimension that orients reform toward justice, balance, and prosperity as public goods. With this framework, reform can be pursued methodically: grounded in revelation, methodologically valid, and responsive to contemporary multicultural realities. The article thus positions Islamic legal philosophy not as abstract discourse, but as a practical foundation for consistent and context-sensitive renewal.